Diseño y construcción de un micro robot para resolución de laberintos. - Puglla Morocho, Noe Ronaldo (2022)
This research project refers to the design and construction of a micro robot for maze solving prototype, capable of navigating and traversing unknown mazes using three distance sensors. For this reason, a review of the solving labyrinths algorithms commonly used in mobile robotics will be carried out, in order to analyze and select which are the best in the implementation in our robot, for this, various software’s were used in order to run a simulation of different algorithms used to solve labyrinths as is the case with Karel and Tinkercad software, the algorithms that are simulated are the right-hand algorithm, treumax algorithm, random algorithm, left hand algorithm. The robot design was inspired to have the smallest possible dimensions taking advantage of all the spaces that are going to be used in the robot, for this the design of chassis and assembly of all components through SolidWorks CAD software, the programming of said robot will be through the IDE of the Arduino software, in addition it will be carried out a selection of the components that are necessary for the robot operation. The design and construction of the labyrinth is focused with the purpose that its routes or paths can be modified in this way that this labyrinth serves us to carry out different tests to the robot in decision making. Finally, the construction and design of the micro robot subjecting it to decision-making tests within the constructed labyrinth. Key words: Mobile robotics, labyrinth robot, design, microcontrollers, autonomous, algorithms, Arduino, SolidWorks.